Novels and essays - Norris, Frank 1870-1902 (New York : The Library of America, 1986)
Vandover and the Brute.
McTeagne.
The Octopus.
Essays.
Contenido : <Vandover and the Brute> <McTeagne> <The Octopus> <Essays>
Keywords: ESTADOS UNIDOS; LITERATURA AMERICANA USA; NOVELA; ENSAYO; CAJA 2